Midaortic syndrome may be a cause of systemic hypertension in Turner syndrome [Midaortik sendrom Turner sendromunda sistemik hipertansiyonun nedenlerinden biri olabilir] - (:unkn) unknown (Cocuk Sagligi ve Hastaliklan Dergisi, 2016)
Middle aortic syndrome (MAS) is characterized by diffuse narrowing of abdominal or distal thoracic aorta and may be associated with genetic syndromes. A case of MAS accompanying Turner's syndrome is presented in this article. A 12-year-old patient with Turner Syndrome was referred because of systemic hypertension. Physical examination revealed II-III/VI grade murmur at right sternal border. Right femoral pulse was nonpalpable, left was weak. Blood pressure at upper extremities was 120/80 mmHg. Telecardiogram showed dilated aortic root. Electrocardiogram revealed left ventricule hypertrophy. Echocardiography showed bicuspid aortic valve, mild aortic stenosis, tortuosity and incrased flow velocity in descending thoracic aorta without diastolic tail. Catheter-angiography demonstrated tortuosity of descending aorta without pressure gradient between proximal and distal parts. Aortogram showed diffuse narrowing of distal thoracic and abdominal aorta. Follow-up with antihypertensives was planned. MAS is a known entity, association with Turner syndrome is rare. Our case gives a new perspective for evaluation of hypertension in Turner's syndrome.
Keywords: Coarctation of aorta; Midaortic syndrome; Systemic hypertension; Turner's syndrome